Failure analysis and solution study of 203 mm solid expandable tubular. (December 2019) - Liao, Xingsong; Qi, Yuekui; Zhu, Xiaohua; Cheng, Feilong; Fu, Daqi; Shi, Changshuai; Huang, Manliang; Qin, Feixiang
Abstract: The solid expandable tubular technology (SETT) is a permanent radial plastic deformation of the casing, which serves to block the leaking section and subsidize the casing. The difficulty of the SETT lies mainly in the material selection of the solid expandable tubular (SET) and the design of the expansion cone structure. The 20G steel casing pipe with 203 mm × 10 mm specification in dagang oilfield is subject to an expansion test with a variable-diameter expansion cone (an expansion rate of 20.2%), during which the casing pipe ruptured and failed. In this paper, the microstructure is analyzed by scanning electron microscope (SEM) and the failure analysis of SET is studied macroscopically by finite element analysis method, and the corresponding solution is proposed. The research shows that when the expansion ratio is 20.2% and the 20G steel casing is used as the material of SET, the maximum stress of SET during the expansion process exceeds the ultimate tensile strength of the material, the SET fracture fails, and 20G steel pipe is not suitable for use as materials of SET in the case of a large expansion ratio (20.2%). In this paper, the expansion cone is continuously optimized. It is found that the single-stage expansion cone is more conducive to the expansion operation than the variable-diameter expansion cone. The expansion cone chamfer and friction coefficient have a significant influence on the driving force, and should be fully lubricated during the expansion operation. In addition, this paper also prefers 316L steel material with better plasticity and toughness. It is found that 316L can expand successfully without failure at large expansion ratio. The research results provide a theoretical basis for the material selection of SET and the structural design of the expansion cone, and have important significance for ensuring the success of the expansion work. Highlights: The reason for the failure of the solid expandable tubular was found by comparison between experiment and simulation. Find the advantages and disadvantages of the variable-diameter expansion cone and the single- stage expansion cone by simulation, in the case of large expansion ratio of 20.2%. The cause of failure has a significant relationship with the expansion cone parameters and materials.